Samapta Unit Patrol Efforts to Prevent Matters by a Group of Communities at the Lamongan Police (Indonesian Journal of Police Studies, 2024)
The Indonesian National Police (Polri) is an institution tasked with law enforcement, maintaining public order and security, providing protection and services to the community. Considering these duties, the author was prompted to conduct research, as there is an issue of increasing incidents of group assaults by certain martial arts associations in Lamongan. The research methodology employed involved conducting interviews with relevant sources and utilizing a qualitative approach. Furthermore, this study incorporated management theory and communication theory in carrying out patrol activities. Additionally, legal system theory was utilized to identify factors contributing to the ability of these martial arts associations to carry out assaults. The discussion revealed several factors influencing the occurrences of assaults by these martial arts associations, namely Trigger, Pivotal, Mobilizing, and Aggravating factors. Furthermore, during the patrol operations, it was found that there was a shortage of patrol members conducting surveillance, leading the leadership to request assistance from other units. Based on these findings, regular patrol efforts, particularly during peak times of public security concerns, are necessary. Therefore, the efforts undertaken by the Satuan Samapta involve conducting patrols in areas with potential vulnerabilities.
Keywords: Patroli, Pengeroyokan, dan Sekelompok Masyarakat